2019
DOI: 10.1136/bmjopen-2019-029748
|View full text |Cite
|
Sign up to set email alerts
|

Gendered relationship between HIV stigma and HIV testing among men and women in Mozambique: a cross-sectional study to inform a stigma reduction and male-targeted HIV testing intervention

Abstract: ObjectivesIncreasing and sustaining engagement in HIV care for people living with HIV are critical to both individual therapeutic benefit and epidemic control. Men are less likely to test for HIV compared with women in sub-Saharan African countries, and ultimately have delayed entry to HIV care. Stigma is known to impede such engagement, placing an importance on understanding and addressing stigma to improve HIV testing and care outcomes. This study aimed to assess the gendered differences in the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 28 publications
8
26
1
1
Order By: Relevance
“…Regarding wealth status, the odds of getting tested for HIV/AIDS for the rich males was 58.6% higher than for the poor. Different studies [14][15][16]20,28 also showed that rich people are more likely to accept HIV VCT as compared to the poor. This could be explained by different reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding wealth status, the odds of getting tested for HIV/AIDS for the rich males was 58.6% higher than for the poor. Different studies [14][15][16]20,28 also showed that rich people are more likely to accept HIV VCT as compared to the poor. This could be explained by different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Different studies also show that age, gender, region of residence, marital status, being covered by health insurance, age at first sex, stigma toward the HIV patient, comprehensive HIV knowledge, discussion about HIV with partner, HIV risky behavior, wealth index, educational status, religion, and distance from the nearest health facility were significantly associated with HIV VCT uptake. 9,10,[13][14][15][16][17] Although HIV VCT uptake is alarmingly low among males residing in Ethiopia, existing studies were not done at country level and the contributing factors were not well studied. Therefore, the current study objectives were to determine the status of uptake and identify the predictors of HIV VCT among sexually active males in Ethiopia using the nationally representative 2016 EDHS data.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding wealth status, the odds of getting tested for HIV/AIDS for the rich males were 58.6% higher than the poor. Different studies (14)(15)(16)20,28) also showed that rich people are more likely to accept HIV VCT as compared to poor people. This could be explained by different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported the positive impact of counseling on their ability to see a future with the disease. Given the association of HIV with impending death 60 and high stigma [61][62][63][64] in the region, patients felt overwhelmed after receiving their diagnosis. Healer counseling provided the reassurance that side effects would go away after a short time and offered strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%